Pengaruh Pertumbuhan Ekonomi, Upah Minimum dan Investasi Terhadap Tingkat Pengangguran di Provinsi Kalimantan Selatan - Restiani, Nia; Pahlevi, Khairi (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine the effect of economic growth, minimum wage, and investment partially and simultaneously on the unemployment rate in South Kalimantan Province and to determine the most dominant factor influencing the unemployment rate in South Kalimantan Province. This study uses secondary data obtained from BPS and BKPM South Kalimantan Province. The analytical technique used in this research is multiple linear regression analysis. This study's results indicate that the Minimum Wage variable partially significantly influences the unemployment rate in the province of South Kalimantan with a probability of 0.0010 <0.05. Meanwhile, economic growth and investment do not have a significant effect. The variables of economic growth, minimum wage, and investment simultaneously significantly affect the unemployment rate in South Kalimantan Province; the minimum wage has the most dominant influence on the unemployment rate in South Kalimantan Province.